PENGARUH METODE PEMBELAJARAN BLENDED LEARNING TERHADAP HASIL BELAJAR PADA PEMBELAJARAN PKn SISWA KELAS V SDN 101732 DESA LALANG TAHUN AJARAN 2021/2022 - Mastari Ramadhani (CV. Anugerah Duta Perdana, 2024)
The purpose of this study was to determine the effect of the blended learning method on student learning outcomes in Civics learning at Sd Negeri 101732 Lalang Village. The type of research used in this study was a quasi- experimental study where this study was divided into two groups, namely the experimental group and the control group as a comparison. The population and sample in this study amounted to 28 people.This study uses the product moment correlation analysis technique, homogeneity test and hypothesis testing to find out the differences and comparisons in the blended learning method that is currently being applied to Civics learning. The results showed that the effect of blended learning method learning on student learning outcomes can be seen from the results of hypothesis testing which showed that the results of the pretest were -3.38 <2.048, so there was no significant difference between the experimental group and the control group, while the results of the posttest were 2.582. >2.048 then there is a difference between the experimental group and the control group.